Resonance-forbidden second-harmonic generation in nonlinear photonic crystals - Jin Jicheng (De Gruyter, 2021)
Second harmonic generation through nonlinear nano-photonic structures is important in both classical and quantum applications. It is commonly expected that the second harmonic frequency can always be generated as long as appropriate quadratic nonlinearity is provided by the material and the phase-matching condition is satisfied. Here, we present an anomaly to this common wisdom by showing that second-harmonic dipoles generated in a nonlinear photonic crystal slab can be completely nonradiative. As a result, no energy is transferred from the fundamental frequency to the second harmonic even when the phase-matching condition is satisfied – a phenomenon we call “resonance-forbidden second-harmonic generation”. Through numerical simulation, we identify two mechanisms that can achieve this phenomenon: symmetry protection and parameter tuning. The finite-size effect and the topological origin of this phenomenon are also discussed.